Tinjauan Yuridis Pengangkatan Anak Pekerja Migran Indonesia Di Sabah, Malaysia Dalam Perspektif Hukum Perdata Internasional - Alyah Padmavati; Yuli Agung Nugroho; Muhammad Nur Rokhim (LPPM Universitas Sains dan Teknologi Komputer, 2023)
Bank Indonesia reports that the largest number of Indonesian migrant workers are in Malaysia. Due to this, these workers often get married and even have children in Malaysia. Children born outside Indonesia, especially in Malaysia which has very strict immigration policies regarding citizenship status for children born to foreign parents. In this situation, custody by Malaysian adoptive parents is the solution that is often chosen. By giving custody rights to Malaysian adoptive families, PMI children can be officially recognized as Malaysian citizens. International child adoption is a problem that has foreign elements, so it is very urgent to study this phenomenon from the perspective of private international law. This research refers to the principle of lex fori, where the emphasis is on jurisdictional issues. The research used is a type of normative research which aims to explore legal regulations related to child adoption in an international context. To get a clearer perspective, researchers took a qualitative approach by interviewing three Indonesian workers living in Sabah, Malaysia. These interviews are conducted via telephone or discussion groups to gain a deeper understanding of the issues being faced.